A nexus of educational qualifications and economic prospects for migrants in selected provinces of South Africa - Themba, Baloyi; Jabulani, Makhubele; Frans, Matlakala; Tuelo, Masilo; Motshidisi, Kwakwa; Allan, Mabasa; Enoch, Rabotata; Prudence, Mafa (Penerbit Universiti Kebangsaan Malaysia, 2021)
The end of apartheids, integration into SADC region and reconnection to global economic world resulted in the increase of migration to South Africa. The aim was to identify the qualifications and economic profile of the migrants in relation to entrepreneurial skills that enhance the quality of life and sustainable livelihood of the migrants. The study was qualitative in nature and employed descriptive research design. These methods helped the researchers to understand the experiences and perceptions of migrants on sustainable livelihood and quality of life. The study used a snowball sampling technique, and individual interviews were used to gather information from study participants. Interviewing technique (face-to-face individual interviews) was used within the context of descriptive design. The paper revealed that migrants' entrepreneurial skills play vital role and contributed immensely to the country's economy and improved the quality of life and sustainable livelihoods of migrants. The study revealed that some migrants’ small businesses were established through the support and network with their fellow countrymen. It was further found that these businesses generate income and uplift their livelihood through the flow of remittances to their home countries, they are experiencing robberies and other related crimes. Lastly, it also revealed that there is no link between the qualification and kind of business operated by the migrants. Findings from this study will form part of the policy briefs to relevant stakeholders and the funders (National Institute for Humanities and Social Sciences – NIHSS. Southern Africa and South Africa is experiencing high volumes of migrants for various reasons. The study contributes into the body of knowledge by closing a gap on the link between the educational qualifications and economic profile that enhance sustainable livelihood of migrants.